Unclassifiable pattern of hypopigmentation in a patient with mosaic partial 12p tetrasomy without Pallister–Killian syndrome. Issue 7 (10th May 2017) - Alesi, Viola; Dentici, Maria L.; Restaldi, Fabrizia; Orlando, Valeria; Liambo, Maria T.; Calacci, Chiara; Capolino, Rossella; Digilio, Maria C.; El Hachem, May; Novelli, Antonio; Diociaiuti, Andrea; Dallapiccola, Bruno
Abstract : Pallister–Killian syndrome (PKS‐#OMIM601803) is a multisystem developmental disorder typically due to the presence of an aneuploidy cell line, consisting of a supernumerary tetrasomic chromosomal marker (SCM) arisen from the short arm of chromosome 12 (12p isochromosome). The clinical phenotype, which is strictly related to the percentage and tissue distribution of aneuploid cells, is characterized by craniofacial dysmorphisms, pigmentary skin anomalies, limb shortening, congenital heart defects, diaphragmatic hernia, hypotonia, intellectual disability, and epilepsy. We report on a 4 year‐old girl harboring a 12p partial isochromosome, involving the PKS critical region, affecting about 70% of circulating lymphocytes, urine, and saliva cells and fibroblast from a hyperpigmented skin spot, and 100% of fibroblasts from a hypopigmented skin spot. Interestingly, despite the high proportion of affected cells this patient did not present with PKS, and a pattern of linear and patchy pigmentary mosaicism was the sole clinical manifestation. The present observation suggests that partial 12p SCM can also result in mild phenotypes, and its prevalence in the human population could have been underestimated. Accurate dermatologic evaluation could be a major handle for genetic testing.